2015
DOI: 10.1177/1071100715586181
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Multicenter Evaluation of Allogeneic Bone Matrix Containing Viable Osteogenic Cells in Foot and/or Ankle Arthrodesis

Abstract: Level II, prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…This study sought to stratify these groups out of the entire population and determine if fusion rates and clinical outcomes would be impacted. Similar to the Jones, et al [18], study, the current study demonstrated no notable differences in fusion rates between normal and groups with risk factors. No significant differences in fusion rates were observed between subjects that had diabetes, were greater than 65 years of age, or were obese /morbidly obese as compared to those that were not.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study sought to stratify these groups out of the entire population and determine if fusion rates and clinical outcomes would be impacted. Similar to the Jones, et al [18], study, the current study demonstrated no notable differences in fusion rates between normal and groups with risk factors. No significant differences in fusion rates were observed between subjects that had diabetes, were greater than 65 years of age, or were obese /morbidly obese as compared to those that were not.…”
Section: Discussionsupporting
confidence: 88%
“…However, since harvesting autograft bone results in well-known complications [12][13][14][15], CBA has been used since it lacks the patient morbidity associated with autograft harvest yet shares the three characteristics that are required for effective bone formation, an osteoconductive scaffold, osteoinductive growth factors and osteogenic cells. In a previous publication, the fusion rate using CBA after foot and/or ankle arthrodesis was higher than or comparable to historical autograft fusion rates [18]. For autograft, the per subject fusion rates were 66.4% (91/137) and 75.2% (103/137) at 6 and 12 months, respectively [2].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The Trinity Evolution and Osteocel allografts have been evaluated separately in 3 clinical studies for foot and ankle arthrodesis and lumbar interbody fusion. [15][16][17] However, neither side-by-side comparisons of these products nor comparisons with autograft controls have been performed. Our study indicates that allograft cell preparations do not all perform the same in vivo.…”
Section: Discussionmentioning
confidence: 99%